Conhecimento e tecnologias para educação ambiental: uma construção envolvendo o jogo de areia - Rodrigues, Maria das Dôres Farias (Universidade Federal Rural do Semi-Árido, 2013)
This dissertation is the result of an analysis of how young students aged 9 to 11 years, the 5th Year of the early years of Primary school, transform their perceptions of household waste being involved in an experience of workshops that produce scenarios using the tool set of sand. This is a qualitative study that seeks to produce an exploratory analysis, based mainly on Eco-Systemic Theories, Liberation and Ecological that distinguish the work in environmental education. The workshops descacaram the issue of domestic waste, with scenes built, reported in the large group, this route which was recorded and tracked through the researcher's field journal and in the form of photographs and video images that were considered in the analysis of changes in behavior youth. Situate the work in the field of Environmental Education in transdisciplinary perspective, to maintain a dialogue with authors from other areas seeking to explain how we feel and live daily events. We highlight the field of psychology and psychoanalysis Carl Jung, Dora Kalf, Ruth Ammann and Edna Garcia Levy, in particular in the construction of the tool sandplay. Humberto Maturana, Candida Maria de Moraes and Katia Cavalcanti authors are important, and the last two are inspired by the Biology of Cognition by Humberto Maturana and Francisco Varela to explain how we live, as we know. The theoretical discussion also considered public policies and laws that address the serious problem of solid waste and domestic and destiny in our community. Production of young at different moments of invention and reinvention of scenarios gives visibility to their potential in terms of creativity, a process that comes amid sensitivities and involvement in the game, the playfulness present in an experiment in education. Interact with embedded processes of imagination, reflection, bringing the effect of awakening to issues that are close - the relationship of each young household waste, with the elements of nature -. At the same time, we detacar moments of changes in ways of perceiving, feeling and acting before a serious issue like this garbage we make in research, the size of which is personal and social at the same time. The main focus of the investigation was to follow the changes in both the way the young observe your environment, how to understand himself, his conduct outside the household waste his dwelling place. The work of the teacher and conductor interference was also considered, as did broader reflection on the theme of domestic waste, triggering the construction of a teaching project for school, entitled The simulation of the landfill. The analysis allowed us to observe and understand the transformations of shares of young students and also for teachers interested in conducting research in their classes. These changes in the coordination of actions by involving social and educational work made them produce significant changes in daily activities, small attitudes towards care of their waste at school, these attitudes that change in living
Knowledge and technologies for environmental education: a construction involving the Beach game
Keywords: Workshops; Beach games; Youth; Environmental education; Oficinas; Jogos de areia; Jovens; Educação ambiental; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE